Optimization of Energy Efficiency According to Freud’s Disk Theory Depending on Propel Pitch Angles - Ucar, Ukbe; Bayrak, Zehra Ural; Tanyeri, Burak (Springer Nature, 2023)
Propeller systems are used extensively in many areas, especially in ships, airplanes, air conditioning and wind turbines. Unmanned aerial vehicles (UAVs), which are produced and used intensively nowadays, are also one of the most important areas where propeller systems are used. Thanks to the propeller system, UAVs can hover in the air and move. It is of great importance that the propellers are designed in a stable, efficient and reliable manner. In this study, drone propellers are optimized in terms of energy efficiency by considering Freud’s Disc Theory. For the optimization process, a new mathematical model, which is used for the first time in the literature, is proposed, and the efficiency of the proposed model is analysed by comparing it with the simulation algorithm and real propeller values. As a result of the analysis study, it has been determined that an improvement of 11.84% compared to the real propeller data and 11.39% compared to the simulation results has been achieved in terms of energy efficiency. It is estimated that high efficiency can be achieved by applying the proposed solution approach to other propeller systems. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Mathematical modelling; Optimization; Propeller design; Simulation; Unmanned aerial vehicles